2017
DOI: 10.1080/01612840.2017.1279247
|View full text |Cite
|
Sign up to set email alerts
|

Online Positive Thinking Training Intervention for Caregivers of Individuals with ASD: Necessity, Acceptability and Feasibility

Abstract: Examination of the fidelity and effectiveness of the PTT are the next steps in the refinement of this intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…All studies had similar methodological designs (RCT with baseline data). However, the length of follow-up varied from immediately after the intervention (Auyeung & Mo, 2018; Bekhet, 2017; Layous, Nelson, & Lyubomirsky, 2013), to shorter periods of two weeks (Seear & Vella-Brodrick, 2013), and longer periods of 2 months (Sergeant & Mongrain, 2014; Strachan et al, 2017) and 6 months (Gander et al, 2013; Shapira & Mongrain, 2010). Five articles reported convenience sampling, whereas the rest had purposive samples (e.g., students in Hong Kong, caregivers of people with autism).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All studies had similar methodological designs (RCT with baseline data). However, the length of follow-up varied from immediately after the intervention (Auyeung & Mo, 2018; Bekhet, 2017; Layous, Nelson, & Lyubomirsky, 2013), to shorter periods of two weeks (Seear & Vella-Brodrick, 2013), and longer periods of 2 months (Sergeant & Mongrain, 2014; Strachan et al, 2017) and 6 months (Gander et al, 2013; Shapira & Mongrain, 2010). Five articles reported convenience sampling, whereas the rest had purposive samples (e.g., students in Hong Kong, caregivers of people with autism).…”
Section: Resultsmentioning
confidence: 99%
“…Sergeant and Mongrain (2014) tested a 12-activity optimism intervention, which largely had no effect any outcomes. Bekhet (2017) tested a positive thinking intervention, which had a medium effect on depressive symptoms, and Gander et al (2013) tested an intervention designed to elicit hope (writing about negative events with unintended positive consequences), which had a medium effect on happiness but no effect on depression.…”
Section: Resultsmentioning
confidence: 99%
“…The parents emphasised their desire for psychoeducation, delivered online through interactive information components and direct access to healthcare professionals. Two studies have delivered online psychoeducation to promote problem-focused coping in parents of children on the autism spectrum, yet they were limited in their success, possibly by the small range of topics covered ( Bekhet, 2017 ; Hemdi & Daley, 2017 ). Parents in this study provided a comprehensive set of psychoeducation topics (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, parents enjoyed the ease and convenience of the online intervention, despite some having problems using the technology. Bekhet (2017) reported on a pilot randomised controlled trial exploring the acceptability and feasibility of online PowerPoint presentations on positive thinking training for 64 parents of autistic children in the United States. The participants had split opinions over the most useful content which suggests that interventions should have tailorable content if they are to meet the diverse needs of parents.…”
mentioning
confidence: 99%
“…Previous research with other populations showed that PT training intervention has been associated with increasing the spiritual well-being of patients suffering from coronary artery diseases (Ghodsbin, Safaei, Jahanbin, Ostovan, & Keshvarzi, 2015) and reducing the burden of caregivers of persons with autism spectrum disorders (Bekhet, 2017). Therefore, future research might consider measuring the impact of a PT training intervention designed for caregivers at various care-recipients’ dementia stages and to plan various levels of preventions for clinical implications.…”
Section: Discussionmentioning
confidence: 99%